2020
DOI: 10.1177/1528083720937388
|View full text |Cite
|
Sign up to set email alerts
|

The influence of kenaf contents and stacking sequence on drop-weight impact properties of hybrid laminated composites reinforced polyvinyl butyral composites

Abstract: For the high cost of aramid fibres and the necessity for finding alternatives which are environmentally friendly, a portion of aramid was substituted by woven kenaf at various sequences and thicknesses, to identify the proper arrangement for producing helmet shell. Drop-weight impact tests were conducted on different configurations of 19 layers of kenaf and aramid reinforced polyvinyl butyral film, which were fabricated by the hot press method. Effects of fibre content, layering sequence and energy ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…From the results, it is indicated that fully kenaf composite withstand lower energy than designated energy which were 5 J, 10 J and 15 J and exhibited the opened-loop curve at 5 J, 10 J and 15 J graphs. This result was similar to the results reported by Salman SD, 9 where the pure kenaf composites could not withstand higher impact energy compared to a hybrid composites. According to Majid et al, the oscillatory behaviour of the force in Figure 3(c) happened due to vibrational motions between the impactor and impacted surface.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…From the results, it is indicated that fully kenaf composite withstand lower energy than designated energy which were 5 J, 10 J and 15 J and exhibited the opened-loop curve at 5 J, 10 J and 15 J graphs. This result was similar to the results reported by Salman SD, 9 where the pure kenaf composites could not withstand higher impact energy compared to a hybrid composites. According to Majid et al, the oscillatory behaviour of the force in Figure 3(c) happened due to vibrational motions between the impactor and impacted surface.…”
Section: Resultssupporting
confidence: 91%
“…It can be concluded that G/K/G composite can still resist the impact energy at 10 J while the G/K/K and K/K/K composites experienced penetration by the impactor. Similar to the study reported by Salman SD, 9 it was found that large amount of energy are absorbed by hybrid composites compared to pure composites made of one type of material. Also, Salman’s study had also shown that the layering sequence of alternating the natural fibre mat (kenaf mat - K) and the synthetic fibre (aramid mat – A) mat tend to have better energy absorption compared to stacking the same type of material at one end such as A/K/K.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations